Development of imagery exercises to increase confidence in penalty stroke for EHC (Eleven Hockey Club) male hockey athletes - Meywah Khofifah; Kurniati Rahayuni; Yulingga Nanda Hanief; Supriatna Supriatna (CV Rezki Media, 2022)
Imagery training is needed by EHC (Eleven Hockey Club) hockey athletes in order to increase self-confidence, especially during penalty strokes. The purpose of this study was to develop imagery exercises to increase confidence in video-based format. The method used in this research is the Research and Development (R&D) method with the following steps: needs analysis, product design, expert validation, product revision, small group trial, large group trial and final product. The subjects used in this study were athletes, coaches and expert validators. Development analysis using interview instruments. The product is validated by 3 expert validators: 1 (one) Psychology Expert, 1 (one) Hockey Coaching Expert, 1 (one) Hockey Expert and the results of the validator's assessment showed 89.28% to 100% rate which assign the product are very valid. The video product then tested by a small group of 5 (five) hockey athletes and a large group of 10 (ten) hockey athletes. From the results obtained from the small group trial, namely 80.83% (very valid) and the results from the large group 98.75% (very valid). So it can be concluded that the development of imagery exercises to increase confidence in doing penalty strokes for video-based Hockey athletes is feasible to use.